2014
DOI: 10.1002/jbmr.2274
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Induces Muscle Paralysis and Inhibits Bone Regeneration in Zebrafish

Abstract: Intramuscular administration of Botulinum toxin (BTx) has been associated with impaired osteogenesis in diverse conditions of bone formation (e.g., development, growth, and healing), yet the mechanisms of neuromuscular-bone crosstalk underlying these deficits have yet to be identified. Motivated by the emerging utility of zebrafish (Danio rerio) as a rapid, genetically tractable, and optically transparent model for human pathologies (as well as the potential to interrogate neuromuscular-mediated bone disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…22 Using a combination of motor activity and behavioral assays, we showed that the paralytic effects of BTx in adult zebrafish were site-dependent, transient and focal, mimicking the paralysis observed in both animal and human studies. When subjected to tail fin regeneration, BTx impaired bone outgrowth, patterning and mineral accrual.…”
Section: 61mentioning
confidence: 75%
See 3 more Smart Citations
“…22 Using a combination of motor activity and behavioral assays, we showed that the paralytic effects of BTx in adult zebrafish were site-dependent, transient and focal, mimicking the paralysis observed in both animal and human studies. When subjected to tail fin regeneration, BTx impaired bone outgrowth, patterning and mineral accrual.…”
Section: 61mentioning
confidence: 75%
“…Using this technique, we found that birefringence was significantly decreased in the regenerated bone rays of BTx-treated fish. 22 More recently, by imaging the same fin using Rotopol microscopy and microCT, we showed that birefringence is highly correlated with TMD (Figure 2), except between joints (where there is additional birefringence from the inter-segment ligament 7 ). The development of a rapid (B2 Â to 10 Â faster than microCT), light-based modality for bone mineralization imaging during fin regeneration opens new opportunities for multi-scale and systems-based investigations in this system.…”
Section: Quantitative Bone Imaging In the Regenerating Zebrafish Finmentioning
confidence: 81%
See 2 more Smart Citations
“…Studies were conducted in mixed sex adult zebrafish. WT ARO and AB fish were obtained from Aquatic Research Organisms (Recidoro et al, 2014) and the Zebrafish International Resource Center (ZIRC, http://zebrafish.org), respectively. opallus b1071 (McMenamin et al, 2014) and pissarro utr8e1 (Quigley et al, 2004) were isolated in forward genetic screens.…”
Section: Zebrafish Rearingmentioning
confidence: 99%